2009
DOI: 10.1108/02686900910966512
|View full text |Cite
|
Sign up to set email alerts
|

The association between auditor quality and human capital

Abstract: PurposeFollowing the high profile collapses of Enron and WorldCom, and the demise of Andersen, human capital (HC) has become a key driver of auditor quality. The purpose of this study is to investigate if there is a positive association between HC and auditor quality in public accounting firms and if the extent of association varies between accounting firms.Design/methodology/approachMultiple regression and logistic modeling are applied to examine the association between auditor quality and HC. The sample cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 14 publications
3
49
0
6
Order By: Relevance
“…Using data from audit engagements performed in The Netherlands, Van Buuren and Causholli (2015) also find strong evidence that partner industry specialization is associated with a greater likelihood of detecting misstatements, and partners with greater industry specialization are more likely to discover misstatements that are subjective in nature, and are more likely to issue modified opinions. Education, experience with the Big N, qualification, and continued education and training have also been shown to positively affect audit quality (Gul, Wu, and Yang 2013;Chen, Liu, and Chien 2009). Academic research in general supports the design and implementation of a dynamic and market-driven accounting and business curricula to educate and train the next generation of accountants with a keen focus on diversity and ethics in the accounting profession.…”
Section: Human Capital and Audit Qualitymentioning
confidence: 99%
“…Using data from audit engagements performed in The Netherlands, Van Buuren and Causholli (2015) also find strong evidence that partner industry specialization is associated with a greater likelihood of detecting misstatements, and partners with greater industry specialization are more likely to discover misstatements that are subjective in nature, and are more likely to issue modified opinions. Education, experience with the Big N, qualification, and continued education and training have also been shown to positively affect audit quality (Gul, Wu, and Yang 2013;Chen, Liu, and Chien 2009). Academic research in general supports the design and implementation of a dynamic and market-driven accounting and business curricula to educate and train the next generation of accountants with a keen focus on diversity and ethics in the accounting profession.…”
Section: Human Capital and Audit Qualitymentioning
confidence: 99%
“…Another effort which the regulators have committed to meet the challenges of the changes in the auditing profession and may increase the AQ is by having CPD program [22]. The objective is to encourage the culture of continuous learning among professionals [21].…”
Section: Continuous Training Programsmentioning
confidence: 99%
“…Some authors in their various studies suggested the examination of the effect of HC on IAO. Cheng et al (2009) revealed that HC has been considered as valuable assets in the public accounting firms. Thus, Public accounting firms should train employees to work as per legal requirements, standards and public's anticipations.…”
Section: Introductionmentioning
confidence: 99%
“…Gray and Manson (2005) agreed with Dang (2004) when he stated that the role of an auditor is to monitor, secure accountability and provide unbiased opinions. Besides, the public concern about auditor's report has been shifted from audit firms to auditee companies, as according to Cheng et al (2009), the auditors' quality to fulfil their responsibilities is a part of their characteristics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation